True knowledge vs empowering knowledge: conceptualizing a theory of mindfulness and knowledge transfer (TMKT) - Issac, Abraham Cyril; Dhir, Amandeep; Christofi, Michael (My University, 2024)
Purpose: Mindfulness is the human ability to be fully present, aware of where we are and what we're doing. This study explores on the impact of mindfulness on different elements of knowledge management, knowledge creation, knowledge sharing and knowledge hiding. Design/methodology/approach: The authors undertake an inductive reasoning approach whereby they try to generate themes from specific observations and conceptualize the theory of mindfulness and knowledge transfer. Findings: This study finds out that mindfulness critically facilitates an open environment and enhances the clarity of thought which aids in effective knowledge creation. Such a realistic understanding about the present scenario encourages employees to share knowledge and equips them to collaborate and effectively work in teams. Surprisingly, this study also finds that mindfulness increases the result orientation to the extent that employees tried to hide knowledge from their co-workers targeting certain self-desired outcomes. In other words, similar to knowledge creation and knowledge sharing, mindfulness increases agenda-based knowledge hiding. Originality/value: The theory of mindfulness and knowledge transfer states that mindfulness increases knowledge creation, knowledge sharing and agenda-based knowledge hiding.
Keywords: Mindfulness; Knowledge creation; Knowledge sharing; Knowledge hiding; Leadership; Covid-19